Subjective socioeconomic status predicts self-rated health irrespective of objective family socioeconomic background - Präg, P (SAGE Publications, 2020)
Aim: Subjective appraisals of socio-economic status (SES) are robustly associated with health outcomes, even when controlling for objective SES. Is this because objective SES is not accounted for in a sufficiently exhaustive way?